IMPLEMENTATION OF COOPERATION RELATIONS BETWEEN INDONESIA AND AUSTRALIA IN THE SOUTH CHINA SEA SECURITY CONFLICT 2019–2023 - Ghalib, Shaliq Khaliq; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The research aims to explain how the implementation of bilateral cooperation relations between Indonesia and Australia in Facing South China Sea Security Conflicts in 2019-2023.The conflict occurs due to the emergence of China as with its aggressive foreign policy in an effort to dominate the Indo-Pacific Region, especially the South China Sea.The People’s Republic of China’s hegemony in the South China Sea constitute a geopolitical threat and disrupt stability in the South China Sea. This research uses a descriptive qualitative approach based on literature studies that uses several data collection methods in the form of documents, journals, research reports, archives, and electronic media derived from the official website based on formal and informal forms. This research uses the perspective of neorealism, Theory of cooperation, and the level of national analysis. The results show that the implementation of Indonesia’s Defense and Security Cooperation with Australia is increasing with the signing of the new Defence Cooperation Agreement to be more comprehensive at the seventh 2+2 Meetings on September 9 2021.The Indonesian government overcomes China’s presence in the South China Sea Region by presenting external parties,such as Australia as a balancing party in the region, aimed at countering the People’s Republic of China dominance in the South China Sea. Keywords: Bilateral Relations,South China Sea,People’s Republic of China, Indonesia, Australia